The extracellular vesicles in HIV infection and progression: mechanisms, and theranostic implications - Tang, Zhen; Lu, Yao; Dong, Jiu-Long; Wu, Wen; Li, Jian (Frontiers in Bioengineering and Biotechnology, 2024)
titled "The Extracellular Vesicles in HIV Infection and Progression: Mechanisms, and Theranostic Implications," is a pertinent addition to Frontiers in Bioengineering and Biotechnology, aligning with its emphasis on nanobiotechnology. We explore the pivotal role of extracellular vesicles in HIV, a subject at the journal's forefront. Our review fills a critical gap in HIV research, enhancing understanding and introducing novel theranostic approaches with extracellular vesicles. This work, transformative for HIV diagnosis and treatment, is set to contribute substantially to the journal's discourse, appealing to its wide readership and advancing the field significantly.